Relationship Between Diet, Tinnitus, and Hearing Difficulties. Issue 2 (March 2020) - Dawes, Piers; Cruickshanks, Karen J.; Marsden, Antonia; Moore, David R.; Munro, Kevin J.
Abstract : Objectives: Diet may affect susceptibility of the inner ear to noise and age-related effects that lead to tinnitus and hearing loss. This study used complementary single nutrient and dietary pattern analysis based on statistical grouping of usual dietary intake in a cross-sectional analysis of tinnitus and hearing difficulties in a large population study sample. Design: The research was conducted using the UK Biobank resource. Tinnitus was based on report of ringing or buzzing in one or both ears that lasts more than five minutes at a time and is currently experienced at least some of the time. Identification of a hearing problem was based on self-reported difficulties with hearing. Usual dietary intake and dietary patterns (involving statistical grouping of intake to account for how foods are combined in real-life diets) were estimated based on between two and five administrations of the Oxford Web-Q 24-hour dietary recall questionnaire over the course of a year for 34, 576 UK adult participants aged 40 to 69. Results: In a multivariate model, higher intake of vitamin B12 was associated with reduced odds of tinnitus, while higher intakes of calcium, iron, and fat were associated with increased odds (B12, odds ratio [OR] 0.85, 95% confidence interval [CI] 0.75 to 0.97; Calcium, OR 1.20, 95% CI 1.08 to 1.34; Iron, OR 1.20, 95% CI 1.05 to 1.37; Fat, OR 1.33, 95% CI 1.09 to 1.62, respectively, for quintile 5 versus quintile 1). A dietary pattern characterised by high protein intake was associated with reduced odds of tinnitus (OR 0.90, 95% CI 0.82 to 0.99 for quintile 5 versus quintile 1). Higher vitamin D intake was associated with reduced odds of hearing difficulties (OR 0.90, 95% CI 0.81 to 1.00 for quintile 5 versus quintile 1), as were dietary patterns high in fruit and vegetables and meat and low in fat (Prudent diet: OR 0.89, 95% CI 0.83 to 0.96; High protein: OR 0.88, 95% CI 0.82 to 0.95; High fat: OR 1.16, 95% CI 1.08 to 1.24, respectively, for quintile 5 versus quintile 1). Conclusions: There were associations between both single nutrients and dietary patterns with tinnitus and hearing difficulties. Although the size of the associations was small, universal exposure for dietary factors indicates that there may be a substantial impact of diet on levels of tinnitus and hearing difficulties in the population. This study showed that dietary factors might be important for hearing health. Abstract : Supplemental Digital Content is available in the text.